The Real Cost of a CPU Hour. - Walker, Edward (Computer (00189162), 2009)
The article presents a modeling tool that lets firms compare the cost of leasing CPU time through cloud computing services with that of acquiring an information-technology service cluster. Cloud computing services are available from a number of vendors including Amazon.com and Google Inc. at a quoted price per CPU hour. Using net-present-value techniques the author shows how to calculate the value of a purchased server cluster, then derives formulas for the cost of one CPU hour in the separate cases of a purchase, a lease, and a purchase-upgrade. INSET: CALCULATING A PURCHASED SERVER CLUSTER'S NET PRESENT VALUE.